Giant cavernous malformation in the child - Rajendra Shrestha; Reeka Pradhan; You Chao (Romanian Neurosurgery, 2012)
Cerebral cavernous malformations (CCMs) are rare lesions that occurs 5 to 13% of all intracranial vascular malformations, develop in 0.02-0.13% of the population. Extra axial cavernous Malformations are even more rare and estimated to be 0.4 to 2% of all the intra cranial cavernous hemangiomas. CCMs that are greater than six cm in size have been described as “giant” in the literature. We report ten year-old male who presented with right lower limb weakness and recurrent seizure disorder. The computed tomography and the magnetic resonance imaging scans demonstrated giant vascular malformation (10CM x 8CM x 6CM) on left parietal lobe. Surgical excision of a giant cavernous malformation (GCM) was performed with good surgical skills. To the best of our knowledge, such large GCMs are extremely rare lesion seen in neurosurgical practice.